Perbandingan Perilaku Disiplin Siswa Sebagai Damapk Teaching Personal and Social Responbility (TSPR) pada Ekstrakulikuler Bulu Tangkis dengan Ekstrakulikuler Paskibra di SMPN 2 Karawang Barat - Firmansyah, - (2018)
The purpose of this study was to compare the application of Teaching Personal and Social Responbility on extracurricular activities extracurricular paskibra with badminton against behavior discipline students in SMPN 2 Karawang West. The method used is the method of experimentation. The population in this research totalled 20 extracurricular participants badminton and 20 extracurricular paskibra, students are drawn using random sampling techniques. Based on the test results the analysis of the data obtained t-female 1.361111 < 2.168252 table then t ho accepted means there is a comparison of the impact of Teaching disciplines of Personal behavior and Social Responbility (TPSR) on a Badminton-playing with extracurricular paskibra in junior high N 2 Karawang West-----Tujuan penelitian ini adalah untuk membandingkan penerapan Teaching Personal and Social Responbility pada ekstrakurikuler bulutangkis dengan ekstrakurikuler paskibra terhadap perilaku disiplin siswa di SMPN 2 Karawang Barat. Metode yang digunakan adalah metode eksperimen. Populasi dalam penelitian ini berjumlah 20 peserta ekstrakurikuler bulutangkis dan 20 ekstrakurikuler paskibra, siswa diambil dengan menggunakan teknik random sampling. Berdasarkan hasil pengujian analisis data diperoleh t-hitung 1,361111 < t tabel 2,168252 maka ho diterima artinya terdapat Perbandingan perilaku disiplin dampak Teaching Personal and Social Responbility (TPSR) pada ekstrakurikuler bulutangkis dengan ekstrakurikuler paskibra di SMPN 2 Karawang Barat